Survey on termite prevalence and management strategies in eastern Uganda - Kagoda, Frank; Ocwa, Akasairi; Najjoma, Dennis; Mufumbiro, Paul; Basena, Emmanuel; Mudingotto, Pyan Joshua (Acta Agraria Debreceniensis, 2025)
Termites are among the most destructive maize pests worldwide. A significant amount of research has been conducted on termites in Uganda but information on the incidence of termites is rarely updated. However, termite incidence, and associated perceptions in different geographical areas is important for development of sustainable control strategies. Therefore, this study was conducted to ascertain the prevalence of termites in Eastern Uganda and the possible ways to control their damage to crops. Data was collected from 272 respondents using face to face interviews following a questionnaire in the nine districts of Pallisa, Mayuge, Manafwa, Bugiri, Butaleja, Sironko, Kapchorwa, Bukwo and Luuka. Results showed that termite prevalence was very high in all districts with some recording 100%. Termites belonging to Macrotermes spp. predominantly affected maize. Mixed responses were recorded on cropping system effect on termite infestation implying that respondents couldn’t tell easily whether the cropping system reduced/increased termite attack. Percentage lodging due to termite attack was significantly higher (P=0.026) in late planted maize. The most dominant termite control strategy among the maize farmers was use of chemicals. Close to 50% of the respondents had never received any information on termites prevalence and management. Therefore, the study recommends more sensitization of farmers on management of termites with emphasis on cost effective and environmentally friendly management practices especially integrated termite control.